2011
DOI: 10.1371/journal.pone.0021205
|View full text |Cite
|
Sign up to set email alerts
|

SCFAs Induce Mouse Neutrophil Chemotaxis through the GPR43 Receptor

Abstract: Short chain fatty acids (SCFAs) have recently attracted attention as potential mediators of the effects of gut microbiota on intestinal inflammation. Some of these effects have been suggested to occur through the direct actions of SCFAs on the GPR43 receptor in neutrophils, though the precise role of this receptor in neutrophil activation is still unclear. We show that mouse bone marrow derived neutrophils (BMNs) can chemotax effectively through polycarbonate filters towards a source of acetate, propionate or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
212
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(225 citation statements)
references
References 30 publications
11
212
1
1
Order By: Relevance
“…Fermentable carbohydrates such as acetate, propionate, and butyrate, which enter the colon and are converted into SCFAs, are a well-studied example of microbial-derived metabolites. Primary SCFAs have a number of physiologic effects, including reduction of food intake, improvement of glucose tolerance, modulation of lymphocyte and neutrophil function, and activation of epithelial cell signaling pathways (15,(123)(124)(125)(126)(127). Signaling through GPCRs, as well as transport of SCFAs by SLC5A8 and the resultant physiological effects, are affected by dietary intake of fermentable fiber (128).…”
Section: Effect Of Interventions Targeting the Gut Microbiotamentioning
confidence: 99%
“…Fermentable carbohydrates such as acetate, propionate, and butyrate, which enter the colon and are converted into SCFAs, are a well-studied example of microbial-derived metabolites. Primary SCFAs have a number of physiologic effects, including reduction of food intake, improvement of glucose tolerance, modulation of lymphocyte and neutrophil function, and activation of epithelial cell signaling pathways (15,(123)(124)(125)(126)(127). Signaling through GPCRs, as well as transport of SCFAs by SLC5A8 and the resultant physiological effects, are affected by dietary intake of fermentable fiber (128).…”
Section: Effect Of Interventions Targeting the Gut Microbiotamentioning
confidence: 99%
“…FFA2 agonists are reported to inhibit lipolysis and regulate plasma free fatty acid levels [95], enhance glucose uptake in adipocytes [85] and stimulate GLP-1 release [96]; all properties indicating that agonism of FFA2 may be beneficial for metabolic conditions. However, FFA2 agonists, including the allosteric compound 14, also promote neutrophil chemotaxis [93,97], a property potentially detrimental in inflammatory conditions. Indeed, FFA2 -/-mice were protected against tissue damage in a model of colitis [93], suggesting FFA2 antagonists, and not agonists, might be useful therapeutically for inflammation.…”
Section: Allosteric Ligands For Ffa2 and Ffa3mentioning
confidence: 99%
“…Since more than 95% of SCFA is absorbed in the intestines, it is much too difficult to determine the concentration of SCFA [88].…”
Section: Microorganisms That Decompose Polysaccharidementioning
confidence: 99%
“…Many studies have found physiological and pathological conditions of intestinal microorganisms and demonstrated that microorganisms and their products play an important role in the gastrointestinal tract, adipose tissue, immune system, and nervous system [20,59,87]. When the distribution of intestinal microorganisms is changed, the concentration of substances that are generated and secreted by microorganisms is changed, which contributes to conditions in which illnesses may break out, such as IBD, colon cancer, obesity, and type 1&2 diabetes [18,59,87,88]. The SCFA concentration in the gastrointestinal tract and blood is effective to prevent such diseases as IBD, cancer and diabetes [20,34,59,86].…”
Section: Regulation Of Inflammation By Butyratementioning
confidence: 99%
See 1 more Smart Citation